DESIGN PERENCANAAN PEMBANGUNAN PUSKESMAS DENGAN FASILITAS RAMAH LINGKUNGAN DI KELURAHAN TALANG KELAPA - Riansyah, Ferdy Fajar; Firdaus, Firdaus (Ensiklopedia Research and Community Service Review, 2025)
The design and planning of a health center (Puskesmas) with environmentally friendly facilities focuses on creating a sustainable healthcare environment that minimizes negative impacts on the ecosystem. This includes the incorporation of green building materials, the use of solar energy systems, rainwater harvesting, and energy-efficient technologies. The design also promotes indoor air quality through natural lighting and ventilation, while reducing water consumption and waste generation. The goal is to build a health facility that not only provides quality healthcare services but also contributes to environmental preservation, offering a healthier and more sustainable living space for the community.Keywords:Community Health Center,Environmentally Friendly facilities,Environmentally friendly materials,Lighting natural ventilation,Environmental conservation,Public health